Peran Bimbingan Rohani Dalam Menumbuhkan Spiritual Penerima Manfaat Di Sentra “Margo Laras” Di Pati - Arum; Kawakib, Nurul; Jamaluddin Muqoffi, Ahmad; Nasihah, Dina; Aryanti, Nisya (At-Taujih : Bimbingan dan Konseling Islam, 2025)
Abstract : This study aims to determine the role of spiritual guidance in fostering the spiritual strength of beneficiaries at the Pati “Margo Laras” Center. Spiritual guidance is one of the services provided to help beneficiaries to have inner peace, discipline in worship, and better behavioral changes in independence in carrying out activities. This research uses descriptive qualitative methods, with data collection techniques through observation, interviews, and documentation. The results showed that spiritual guidance has a positive impact in shaping a stronger spiritual attitude, such as increased motivation to worship, the emergence of a sense of calm and patience, and self-awareness in living life Activities such as congregational prayer, reading the Qur'an, and religious tausiyah are effective media in fostering mental and emotional beneficiaries This guidance also helps them in the process of social adaptation and instills moral and religious values as a provision for life after the rehabilitation period. Thus, spiritual guidance plays an important role in supporting the recovery process and overall spiritual strengthening of beneficiaries. Keywords: Spiritual Guidance; Spiritual; Beneficiaries; Social Rehabilitation.   Abstrak : Penelitian ini bertujuan untuk mengetahui peran bimbingan rohani dalam menumbuhkan kekuatan spiritual penerima manfaat di Sentra "Margo Laras" Pati. Bimbingan rohani merupakan salah satu layanan yang diberikan untuk membantu penerima manfaat agar memiliki ketenangan batin, kedisiplinan beribadah, dan perubahan perilaku yang lebih baik dalam kemandirian melakukan aktivitas. Penelitian ini menggunakan metode kualitatif deskriptif, dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentası. Hasil penelitian menunjukkan bahwa bimbingan rohani memberikan dampak positif dalam membentuk sikap spiritual yang lebih kuat, seperti meningkatnya motivasi untuk beribadah, munculnya rasa tenang dan sabar, serta kesadaran diri dalam menjalanı kehidupan Kegiatan seperti shalat berjamaah, membaca Al-Qur'an, dan tausiyah agama menjadi media efektif dalam membina mental dan emosional penerima manfaat Bimbingan ini juga membantu mereka dalam proses adaptası sosial serta menanamkan nilai-nilai moral dan religus sebagai bekal hidup setelah masa rehabilitası. Dengan demikian, bimbingan rohani berperan penting dalam mendukung proses pemulihan dan penguatan spiritual penerima manfaat secara menyeluruh Kata Kunci: Bimbingan Rohani; Spiritual; Penerima Manfaat; Rehabilitasi Sosial.